Recovery of Heavy Metals from MSW Molten Fly Ash by CIP Method - Alorro, Richard; Hiroyoshi, Naoki; Ito, Mayumi; Tsunekawa, Masami (Elsevier Science BV, 2009)
Molten fly ash (MFA), generated by the melting process of municipal solid waste incineration (MSWI) solid residues in Japan, contains considerable amounts of heavy metals such as Pb, Zn, Cu and Cd. Therefore, MFA is classified as a hazardous waste and needs treatment for detoxification or recovery of heavy metals as secondary sources. Carrier-in-Pulp (CIP) method, which is similar in principle with the Carbon-in-Pulp technology for gold recovery from ores, was proposed to recover these heavy metals from molten fly ash. Unlike the traditional Carbon-in-Pulp process, the carrier or adsorbent in the Carrier-in-Pulp method is not only limited to carbon; other materials such as Fe powder can also be used. Moreover, other physical separation techniques such as magnetic separation can also be employed to harvest the carrier from the leach pulp.The present study, which can be regarded as a batch mode Carbon-in-Pulp process, investigated the application of the CIP technique to recover heavy metals from MSW molten fly ash containing 10.2 wt.% Zn,2.78 wt.% Pb, 0.14 wt.% Cu, and 0.12 wt.% Cd. Granular activated carbon (GAC) was utilized as an adsorbent in batch adsorption tests and experiments involving the CIP method using NaCl as lixiviant. The effects of activated carbon dosage, pH, NaCl concentration, and treatment time were determined. Adsorption tests showed that the competition of metal ions present in a multi-component system suppressed the adsorption of Pb, Zn, Cu and Cd on GAC but the suppression can be minimized by increasing the GAC dosage. Around 90–100% of Pb, Zn, Cu and Cd were extracted from MFA at various conditions. At the optimum conditions (5 kmolm-3NaCl,10 g GAC, pH 5–6, and 3 h treatment time), GAC recovered 57% Zn, 40% Pb, 90% Cu, and 54% Cd. The leaching test confirmed that the extraction of Pb from the CIP-treated residue was below the standard, thus, satisfying the land-filling guidelines in Japan.